Fully synthetic Mincle-dependent self-adjuvanting cancer vaccines elicit robust humoral and T cell-dependent immune responses and protect mice from tumor development. Issue 48 (1st December 2021) - Luo, Xiang; Lian, Qinghai; Li, Wenwei; Chen, Liqing; Zhang, Renyu; Yang, Deying; Gao, Lingqiang; Qi, Xiaoxiao; Liu, Zhongqiu; Liao, Guochao
Abstract : A new strategy based on a Macrophage-inducible C-type lectin (Mincle) agonist was established to construct synthetic cancer vaccines. Abstract : A new strategy based on a macrophage-inducible C-type lectin (Mincle) agonist was established to construct synthetic cancer vaccines. Using sialyl-Tn (STn) as a model antigen, four conjugates with the Mincle agonist as a built-in adjuvant were designed and synthesized through a facile and efficient method. All conjugates could induce BMDMs to produce inflammatory cytokines in a Mincle-dependent manner and were found to elicit robust humoral and T cell-dependent immune responses alone in mice. The corresponding antibodies could recognize, bind and exhibit complement-dependent cytotoxicity to STn-positive cancer cells, leading to tumor cell lysis. Moreover, all conjugates could effectively inhibit tumor growth and prolong the mice survival time in vivo, with therapeutic effects better than STn-CRM197/Al. Notably, compared to conventional glycoprotein conjugate vaccines, these fully synthetic conjugate vaccines do not cause "epitope suppression." Mincle ligands thus hold great potential as a platform for the development of new vaccine carriers with self-adjuvanting properties for cancer treatment. Preliminary structure–activity relationship analysis shows that a vaccine containing one STn antigen carried by vizantin exhibits the best efficacy, providing support for further optimization and additional investigation into Mincle agonists as the carrier of self-adjuvanting cancer vaccines.